An Assessment of Worker Reaction to their Union and Employer Post-Strike: A Canadian Experience - Chaulk, Kimberly; Brown, Travor (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2008)
AbstractUnion members (n = 187) completed surveys assessing five affective measures (organizational commitment, job satisfaction, work climate satisfaction, management satisfaction, and union commitment) following a five-month long strike. Paired t-tests (using retrospective questions where participants assessed pre and post-strike affect on a single survey) found that the strike had a negative impact on worker reactions to both their management group and their union across all five measures. The significance of this study is that the negative effects of strikes can, and do, carry over into the workplace in terms of worker affect towards their union and employer. From a theoretical perspective, these findings are consistent with the IR systems’ concept of a feedback loop and suggest that future strike research and theories should be expanded to examine issues related to worker reaction.